Three-Dimensional Porous Architectures of Carbon Nanotubes and Graphene Sheets for Energy Applications - Wang, Xuewan; Sun, Gengzhi; Chen, Peng (Frontiers in Energy Research, 2014)
Owing to their extraordinary physicochemical, electrical, and mechanical properties, carbon nanotubes (CNTs) and graphene materials have been widely used to improve energy storage and conversion. In this article, we briefly review the latest development on fabrication of 3D porous structures of CNTs or graphene sheets or their hybrids, and their applications in various energy devices including supercapacitors, (bio-) fuel cells, and lithium ion batteries.